A flexible, low-cost and algorithm-independent calibrator for automated blood pressure measuring devices - Pereira, J. M. C. D.; Ribeiro, G.; Postolache, O. (Applied Sciences, 2025)
Arterial hypertension is one of the most important public health problems, especially in developed countries. The quality and calibration of blood pressure (BP) equipment used for non-invasive blood pressure (NIBP) measurement are essential to obtain accurate data that support correct medical diagnostics. This paper includes the hardware and software description of a flexible, low-cost and algorithm-independent calibrator prototype that can be used for the static and dynamic calibration of automated blood pressure measuring devices (ABPMDs). In the context of this paper, the meaning of calibrator flexibility is mainly related to its ability to adapt or change easily in response to different situations in terms of the calibration of ABPMDs that can use a variety of calibration settings without the need to use specific oscillometric curves from different ABPMD manufacturers. The hardware part of the calibrator includes mainly an electro-pneumatic regulator, used to generate dynamic pressure signals with arbitrary waveforms, amplitudes and frequencies, a pressure sensor, remotely connected through a pneumatic tube to the blood pressure (BP) cuff, a blood pressure release valve and analog conditioning circuits, plus the A/D converter. The software part of the calibrator, mainly developed in LabVIEW 20, enables the simulation of oscillometric pressure pulses with different envelope profiles and the implementation of the main algorithms that are typically used to evaluate systolic, diastolic and mean arterial pressure values. Simulation and experimental results that were obtained validate the theoretical expectations and show a very acceptable level of accuracy and performance of the presented NIBP calibrator prototype. The prototype calibration results were also validated using a certified NIBP calibrator that is frequently used in clinical environments.